Hysteresis loops of ferroelectric bilayers and superlattices - Chew, Khian Hooi; Tilley, D.R.; Ong, L.H.; Osman, J. (AIP Publishing, 2000)
A ferroelectric superlattice with an antiferroelectric interfacial coupling is considered; the same model describes a bilayer with antiferroelectric coupling. By mapping minimum points in the Landau free energy expression and plotting them against the applied electric field, a triple hysteresis loop pattern is obtained. The loop patterns vary between typically ferroelectric and typically antiferroelectric depending on the layer thicknesses and the magnitude of the interfacial-coupling constant. This work suggests the possibility of designing multilayer elements for computer memories with four or more different storage states. (C) 2000 American Institute of Physics. [S0003-6951(00)03843-2].